THE ENHANCEMENT oF COOPERATIve ABILITY AND BECOMING A GOOD LISTENER ABILITY IN SOLUBILITy AND solubility product by learning of hypnoteaching METHOD - pazar rakasiwi; noor fadiawati; nina kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The purpose of this research is to describe the effectiveness of improving the cooperative ability and becoming a good listener with using hypnoteaching in solubility and solubility product.The research was done in class XI IPA2 State Senior High School 13 Bandar Lampung. This study used a pre-experimental method with One Shoot Case Study Design. The effectiveness of hypnoteaching is measured by the percentage of average research finding in each meeting.  After observation in five meetings, the average percentage of cooperative ability has improved significantly with percentage 44.85%, 50.00%, 61.25%, 63.53%, and 65.00%. Then, becoming a good listener with percentage 66.67%, 70.56%, 73.13%, 74.71%, and 81.11% has improved significantly too. Therefore, it can be concluded that learning with hypnoteaching is significant to improve cooperative ability and becoming a good listener.Keywords: learning of hypnoteaching, cooperative ability, becoming a good listener.